Simulation of the Implementation of Nursing Discharge Planning to Reduce Patient Recurrence Rates in Hospitals - Suradi Efendi; Nour Sriyanah; Ayu Sri Wahyuni; Elni Putri Olofia Kumape; Viralin Abbas (IJCS: International Journal of Community Service, 2022)
Discharge planning is part of the nursing process and the main function of care that must be carried out by nurses in a structured manner starting from the time the patient enters the hospital. Discharge planning is a regulatory process that helps clients prepare to leave a better level of care, both inside and outside their health facility with the aim that patients and their families can manage post-discharge care independently. The purpose of discharge planning focuses on providing health education to patients to discuss nutrition, drugs, activities or training and special instructions regarding the signs and symptoms of the patient's illness. Before going home, patients and families are given education to be able to manage their condition and/or during recovery. Discharge planning in accordance with the standards must be carried out in the hospital, because discharge planning is an important element in nursing services which aims to make the client independent after leaving the hospital. The method of this community service is the counseling method in the form of direct presentation of lecture material, direct simulation and measuring the level of knowledge of nurses in evaluating the application of nursing discharge planning in order to reduce the recurrence rate of patients in hospitals with the number of nurses in this study namely 28 people.